20 years of Scandinavian studies at Vilnius University − feast, play and puzzles - Sausverde, Ērika (Taikomoji kalbotyra, 2014)
The present review article has been re-published in this electronic journal with kind permission of the author of the article and the editors of the following book: Sausverde, Ērika and Ieva Steponavičiūtė (eds) 2014. Funs and Puzzles in Modern Scandinavian Studies. Vilnius University.
Keywords: none